EFFECT OF BINDER TYPE AND HEATING TIME TO QUALITY OF CONTAINER FROM UNGRADED MUSA BALBISIANA COLLA LEAVES - Suriwong, Voraluck; Swaeng-Ngam, Surintraporn; Inrirai, Patcharaporn (Srinakharinwirot University Journal of Sciences and Technology, 2024)
The aim of this study was to investigate the effect of the binder and heating time on the production of containers made from ungraded banana leaves. Before applying it to dried banana leaves, prepare a binder by combining wheat flour with three varieties of starch: tapioca starch, corn starch, and modified tapioca starch in a 3:1 ratio. It was formed at a temperature of 165ºC with three different heating times: 2 minutes, 2.5 minutes, and 3 minutes to form containers from banana leaves in the shape of round bowl with a diameter of 14 cm and a depth of 4 cm. The results of the investigation into the color properties of banana leaf containers following the molding procedure revealed that the molded containers showed hues of green-yellow. The variation in hue depends on the unprocessed materials prior to the molding process. Additionally, the binder and heating duration did not have any impact on the thickness and density measurements of containers made from banana leaves. There was not significantly difference (p<0.05) seen in the data across all testing conditions. Further, this condition has an impact on the mechanical properties and water absorption of the formed container. The containers produced with the C1 binder at a heating time of 2 minutes showed a substantially higher percentage of shape deformation upon applying force (p>0.05) compared to the containers made with the C2 and C3 binder formulations. Moreover, the extension of the heating time to 3 minutes resulted in a significant decrease in the elasticity of the container, becoming it less resistant to breakage. Consequently, this led to a substantial increase in the percentage of water absorption (p<0.05). In this case, the utilization of containers made from binder formulae C2 and C3, accompanied by a heating time of 2 minutes, seems to be suitable for the molding process. This material shows good tensile strength properties and demonstrates low tensile strain at maximum tensile stress. The molded container that is obtained may be utilized for packaging purposes and enhances the quality of products produced from low-grade Tanee banana leaves.